Comparison of self-reported sleep sufficiency and accelerometer-measured sleep duration in relation to mental health, physical health, and life satisfaction - Ahrensberg, Hannah; Christensen, Anne Illemann; Andersen, Susan; Petersen, Christina Bjørk (Frontiers in Sleep, 2025)
IntroductionSleep is crucial for health and wellbeing, but different dimensions of sleep may affect health differently. This cross-sectional study explores the associations of self-reported sleep sufficiency and accelerometer-measured sleep duration with mental health, physical health, and life satisfaction.Materials and methodsData from 1,022 individuals (age ≥16 years) from the Danish Health and Morbidity Survey in 2023 were used. Mental and physical health were assessed using the SF-12 questionnaire, and life satisfaction with the Cantril Ladder scale. Multiple adjusted linear regression models were used to examine associations separately and in four combined categories: (1) low sufficiency, <7/>9 h (n = 106), (2) low sufficiency, 7–9 h (n = 89), (3) high sufficiency, <7/>9 h (n = 271), and (4) high sufficiency, 7–9 h (n = 556).ResultsDeviations from recommended sleep durations (<7 or >9 h) and low sleep sufficiency were associated with poorer mental health, physical health and life satisfaction, most strongly for mental health and life satisfaction. Specifically, individuals sleeping 7–9 h with low perceived sleep sufficiency had mental health scores of 10.9 points (95% CI: −13.2; −8.6) lower than those sleeping 7–9 h and reporting high sleep sufficiency. Similarly, those sleeping <7/>9 h and reporting low sleep sufficiency had mental health scores 8.5 points (95% CI: −10.8; −6.3) lower.ConclusionRegardless of sleep duration, low sleep sufficiency was consistently associated with poorer health outcomes, suggesting that self-reported sleep sufficiency may be more correlated to health than accelerometer-measured sleep duration alone. These findings underscore the need to integrate multiple sleep dimensions and measurement strategies into public health surveillance.